2014
DOI: 10.1590/0034-737x201461040009
|View full text |Cite
|
Sign up to set email alerts
|

Sanidade de sementes de arroz, biocontrole, caracterização e transmissão de Curvularia lunata em semente-plântula de arroz

Abstract: Sanity of rice seed, biocontrol, characterization and transmission of Curvularia lunata on rice seed-seedlingsThis study evaluates the sanitary quality of rice seeds cultivar Bonança, quantifies the transmission of Curvularia lunata associated with seeds -seedling and evaluates the efficiency of Bacillus spp. isolates for the control of leaf spot. The samples were disinfected and plated, and seed health was evaluated after seven days. After confirmation of pathogenicity, the seedlings inoculated by the sprayin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
2
10
1
1
Order By: Relevance
“…These results are in agreement with Casa et al (2006), who stated that the pathogen makes use of organs or parts of the host for its survival and dissemination. Silva et al (2014) observed results similar to those of the present study in rice seeds when they reported that the fungus Curvularia lunata was detected in all the seedling organs at the three assessment times, where the mean transmission rates in the three periods were 51.75, 44.16 and 73.12 %, for the primary root, stalks and leaves, respectively. Corroborating this study, Casa et al (2006) stated that fungi associated with the seed can cause deterioration, or be transmitted to the seedling, colonizing the root and canopy organs.…”
Section: Quantification Of the Transmission Rate Of The Main Fungi Assupporting
confidence: 91%
“…These results are in agreement with Casa et al (2006), who stated that the pathogen makes use of organs or parts of the host for its survival and dissemination. Silva et al (2014) observed results similar to those of the present study in rice seeds when they reported that the fungus Curvularia lunata was detected in all the seedling organs at the three assessment times, where the mean transmission rates in the three periods were 51.75, 44.16 and 73.12 %, for the primary root, stalks and leaves, respectively. Corroborating this study, Casa et al (2006) stated that fungi associated with the seed can cause deterioration, or be transmitted to the seedling, colonizing the root and canopy organs.…”
Section: Quantification Of the Transmission Rate Of The Main Fungi Assupporting
confidence: 91%
“…The morphological characteristics observed during the microscopic analysis suggested that the fungus genus isolated from Andropogon seeds is Curvularia lunata, similar to that described in the relevant literature (Ellis 1971;Sivanesan 1987). Other authors have also obtained similar results when examining species infecting other plants, for example, rice, Silva et al (2014) and Kusai et al (2016), characterized C. lunata colonies in BDA with cottony appearance and blackish-gray coloration. Also for these authors, the conidia presented three transverse septa, with a more voluminous median cell, pronounced curvature and dark hilum at one end, having average dimensions of 20.62 μm × 8.58 μm.…”
supporting
confidence: 63%
“…Most of these species are pathogenic and give rise to losses in agricultural production. In vegetables, there are several examples of diseases caused by this genus responsible in the main part for necrotic spots in the leaves of several plant families (Dasgupta et al 2005), especially Poaceae (Toledo et al 1990;Yago et al 2011;Silva et al 2014;Santos et al 2014;Kusai et al 2016).…”
mentioning
confidence: 99%
“…Several species of this genus may cause leaf spots, mainly in grasses FURTADO, 2007;YAGO et al, 2011). It may also be transmitted by seedplant (SILVA et al, 2014).…”
Section: Pathogenicitymentioning
confidence: 99%